Poverty, progress, and population - Wrigley, E. A. (Edward Anthony), 1931-2022 (Cambridge University Press, 2004)
Our understanding of what constituted the industrial revolution has changed fundamentally in recent decades. Sir E.A. Wrigley, the leading historian of industrial England, here sets out to expose the inadequacy of what was once the received wisdom and to suggest what he believes should stand in its place.